Temperature and gas concentration measurements with vibrational ultra-broadband two-beam femtosecond/picosecond coherent anti-Stokes Raman scattering and spontaneous Raman scattering - Ran, Yang; Junghanns, Marcus; Boden, Andre; Nolte, Stefan; Tuennermann, Andreas; Ackermann, Roland (Journal of Raman Spectroscopy, 2019)
In combustion and gasification diagnostics, the knowledge of temperature distribution and gas component concentration is crucial in order to understand or optimize such processes. In this study, we compare ultra-broadband two-beam femtosecond/picosecond coherent anti-Stokes Raman scattering (fs/ps CARS) with spontaneous Raman scattering to retrieve temperature and concentration information. We show that two-beam fs/ps CARS can be effectively used for concentration measurements down to 0.5% CO in gas mixtures of CO2 and N2. With two-beam fs/ps CARS, thermometry from 200°C to 800°C based on CARS spectra of CO2 or H2 is shown. With spontaneous Raman scattering, concentration determination is well performed in gas mixtures of H2, N2, and CO2 with H2 content ranging from 16% to 0.5% at room temperature and from 16% to 7% H2 at 900°C. Besides, thermometry in gas mixtures of N2 and CO2 from 200°C to 600°C based on spontaneous Raman scattering is also shown in this study.
CRIS-Team Scopus Importer:2023-04-20
Keywords: CARS; femtosecond; gas; Raman spectroscopy; thermometry